2006
DOI: 10.1128/jvi.80.5.2127-2140.2006
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Proteome: Identification of Proteins in Vaccinia Virus Intracellular Mature Virion Particles

Abstract: Vaccinia virus is a large enveloped poxvirus with more than 200 genes in its genome. Although many poxvirus genomes have been sequenced, knowledge of the host and viral protein components of the virions remains incomplete. In this study, we used gel-free liquid chromatography and tandem mass spectroscopy to identify the viral and host proteins in purified vaccinia intracellular mature virions (IMV). Analysis of the proteins in the IMV showed that it contains 75 viral proteins, including structural proteins, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
228
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(243 citation statements)
references
References 192 publications
12
228
1
1
Order By: Relevance
“…There was no obvious relationship, however, between immunodominance, as assessed by hierarchies of IFN-␥ responder cell numbers (Fig. 6) or the presence of multiple epitopes per ORF (Table II) and protein occurrence in virions (55). A3L, for example, was dominant in subject 2 and contains at least 3 epitopes.…”
Section: Discussionmentioning
confidence: 90%
“…There was no obvious relationship, however, between immunodominance, as assessed by hierarchies of IFN-␥ responder cell numbers (Fig. 6) or the presence of multiple epitopes per ORF (Table II) and protein occurrence in virions (55). A3L, for example, was dominant in subject 2 and contains at least 3 epitopes.…”
Section: Discussionmentioning
confidence: 90%
“…ϩ T cells could be explained by the near complete absence of virulence factors in the virion (30). It is likely that DC take up debris from apoptotic or necrotic VACV-infected cells that might contain VACV virulence factors that theoretically could be presented by DC via MHC class II molecules.…”
Section: Cd8mentioning
confidence: 99%
“…However, most of these studies were limited in their ability to perform a complete structural analysis of all the protein components of the virion, possibly due to the limited availability of advanced purification techniques and the limitations of the technologies available for protein identification at the time of those studies. Ten years later, several studies of the comprehensive structural analysis of the protein composition of the infectious MV of VACV were reported (30,134,179). In one study, by analyzing the proteins in the MV of VACV-WR using a combination of gel-free liquid chromatography and tandem MS (LC-MS/MS), Chung et al identified 75 viral proteins and determined their relative abundances (Table 1) (30).…”
Section: Proteomic Studies Of Poxvirus Virionsmentioning
confidence: 99%